2005
DOI: 10.1016/j.febslet.2005.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Structural and morphological characterization of hemozoin produced by Schistosoma mansoni and Rhodnius prolixus

Abstract: Hemozoin (Hz) is a heme crystal produced upon the digestion of hemoglobin (Hb) by blood-feeding organisms as a main mechanism of heme disposal. The structure of Hz consists of heme dimers bound by reciprocal iron-carboxylate interactions and stabilized by hydrogen bonds. We have recently described heme crystals in the blood fluke, Schistosoma mansoni, and in the kissing bug, Rhodnius prolixus. Here, we characterized the structures and morphologies of the heme crystals from those two organisms and compared them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
146
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(168 citation statements)
references
References 39 publications
18
146
0
4
Order By: Relevance
“…While PfHz and BH SEM images portray a biomineral of elongated rectangular crystals with well-defined crystal facets, SmHz images depict the characteristic heterogeneous morphology and large size distribution often attributed to the extracellular environment of Hz formation in S. mansoni (Fig. 1B) [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While PfHz and BH SEM images portray a biomineral of elongated rectangular crystals with well-defined crystal facets, SmHz images depict the characteristic heterogeneous morphology and large size distribution often attributed to the extracellular environment of Hz formation in S. mansoni (Fig. 1B) [11].…”
Section: Resultsmentioning
confidence: 99%
“…This dark-brown pigment was recently characterized by Oliveira and coworkers as being structurally identical to P. falciparum Hz (PfHz) and its synthetic analogue, β-hematin (BH) [10,11].…”
Section: Introductionmentioning
confidence: 91%
“…It is however pertinent to the question of how the crystal assembles. (Pagola et al, 2000) and haemozoin from Rhodnius prolixus, Schistosoma mansoni (Oliveira et al, 2005) and Plasmodium falciparum (Walczak et al, 2010;Walczak et al, 2011). Using EXAFS, the authors demonstrated that the anhydrides of these two iron porphyrins have similar local order to haemozoin and that this persists in DMSO at least in the case of Fe(III)mesoporphyrin.…”
Section: Haemozoin Formation In Vivomentioning
confidence: 98%
“…The unit cell dimensions of haemozoin from S. mansoni and R. prolixus were determined in 2005 and structures determined by Rietveld fitting of experimental parameters obtained from the Xray powder diffraction pattern collected with synchrotron radiation (Oliveira et al, 2005). In this study, the atomic coordinates reported for the original -haematin structure were used and only the unit cell and profile parameters were refined.…”
Section: Haemozoin Formation In Vivomentioning
confidence: 99%
See 1 more Smart Citation